Principles of care for adolescent girls with eating disorders and body disturbances disorders: lessons from the COVID-19 pandemic - A. A. Pichikov; Y. V. Popov; Y. A. Yakovleva; T. A. Salomatina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
The pandemic of the new coronavirus infection (COVID-19) has contributed to an increase in problems related to eating behavior and body image in the population. Various risk factors that have become relevant due to changes in the usual lifestyle have significantly affected the frequency of eating disorders in the adolescent population. This necessitated the adapting of new strategies for providing medical care in conditions of limited personal contact.The aim of the work is the methodological substantiation and systematization of modern approaches to the prevention and treatment of eating disorders, body image disorders and risk factors associated with them in adolescents in the conditions of the COVID-19 pandemic.Materials and methods. The methodological basis of the work is a comprehensive analysis of modern medical and social approaches and recommendations on the organization of assistance to adolescents with eating disorders and body image disorders, with a description of personal experience of using various interventions on an outpatient basis during the pandemic.Results: Prevention and treatment of eating disorders and body image disorders in adolescents during the pandemic should be aimed at specific risk factors those have proved to be the most relevant in connection with restrictive measures: involvement in body image-related social media content and active use of the media; reduction of physical activity with simultaneous increase in access to food; social isolation and reduction of social support; restriction of access to qualified care. The most reasonable approaches during the pandemic are the approaches focused on the family of a teenager using, if possible, remote forms of assistance.Conclusions: Currently, there are no norms and standards in the organization of assistance to adolescents with eating disorders and body image disorders in the pandemic context. However, the analysis of the implemented approaches aimed at various risk factors of these disorders will allow the use of the most effective preventive and therapeutic practices in the future.